Lexic-semantic features of some toponyms of the region of aghdam summary - Aлиевa, A. (Journal of Oriental Studies, 2018)
In this article the toponyms of the region of Aghdam of Azerbaijan had been investigated by lexically-semantically. The investigation of toponyms of the region of Aghdam gives an understanding that this place is an ancient resident of Turkish peoples. It had been mostly proved with more examples of typical forms with suffixes li, lu, lar, ler. The ethimological explanation of some characterical toponyms of the area of Aghdam had been given, and grammatical features had been explained.